Revenge porn sebagai Kejahatan Kesusilaan Khusus: perspektif Sobural - Christianto, Hwian (Veritas et Justitia, 2017)
Revenge porn is a new growing modus operandi of crime in society. Law enforcement still considers porn revenge as a pornographic crime in general as it is an activity of disseminating information that violates decency. Approach used by law enforcement in assessing revenge porn is still limited to  formal juridical approach without considering the characteristics of porn revenge that substantive justice is not fulfilled. As part of a full understanding of porn revenge, a Criminological understanding of the Sobural approach is made. Two issues to be studied are (1) what is the significance of using the Sobural approach? And  (2) Is revenge porn a decency crime based on the Sobural approach? Empirical  juridical research method is used in this study by basing on a primer in the form of legislation supported by criminal law theory related to revenge porn. Exposure from primary data is associated with secondary data in the form of Judge Judgment to see understanding of defeating of revenge porn by a judge.  The results of the study show that criminological understanding of porn revenge provides a very significant different approach in criminal law. Revenge porn is judged by the context of the community in which the perpetrators and acts of revenge porn are performed. Sobural (Social, Cultural and Structural) approach affirms contextual assessment of porn revenge based on social values, cultural values and structural factors of society. The approach of these three elements has a close correlation with the moral norms as the measure of defamation of crime of pornography as a decency crime. The integration of the Sobural approach to the understanding of moral norms in assessing porn revenge will provide an opportunity for the enforcement of living laws in society.